Python package for icequakes inversions - Moreau Ludovic (Zenodo, 2023)
This package was used to process seismic data recorded on sea ice in Svalbard (Norway), in March 2019. The inversion determines the position of the icequake source and sea ice thickness. More details in: Moreau et al,Analysis of microseismicity in sea ice with deep learning and Bayesian inference: application to high-resolution thickness monitoring, The Cryosphere (2023):https://doi.org/10.5194/tc-2022-212